ANALYSIS OF THE HEALTH CARE SYSTEM OF PAKISTAN: LESSONS LEARNT AND WAY FORWARD - Kurji, Zohra; Premani, Zahra Shaheen; Mithani, Yasmin (Journal of Ayub Medical College Abbottabad, 2016)
Background: Pakistani health care system is in progress and since last year, Pakistan has tried to make much improvement in its health care delivery system and has brought out many reforms. Methods: A systematic search of national and international literature was looked from peer-reviewed databases form MEDLINE, CINAHL, and PubMed. Results: There are few strengths in health care delivery system in Pakistan like making health policies, participating in Millennium Development Goals program, initiating vertical programs and introducing Public Private Partnership, improving human resource development and infrastructure by making Basic Health Unit and Rural Health Centres. However, these all programs are very limited in its scope and that is the reason that Pakistan’s healthcare system is still not very efficient. There are numerous weaknesses like poor governance, lack of access and unequal resources, poor quality of Health Information Management System, corruption in health system, lack of monitoring in health policy and health planning and lack of trained staff. Conclusion: Pakistan is improving very slowly in the health sector for the last five decades as is evident by its health indicators and above mentioned strengths and weaknesses. Therefore, the Government needs to take strong initiatives to change the current health care system. Keywords: health care delivery system, Millennium Development Goal, Public Private Partnership, Basic Health Unit (BHU) and Rural Health Centres (RHC)